2015
DOI: 10.2214/ajr.14.12750
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CT Examinations in Children With Suspected Acute Appendicitis in the Community Setting: A Need for More Education

Abstract: CT parameters and radiation doses from single-phase examinations in children with appendicitis were similar at nonpediatric treatment centers and a tertiary care children's hospital. Future educational outreach should focus on optimizing other technical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Currently, over 50 % of children undergoing appendectomy in North America have radiation based imaging [ 38 ]. This rate is too high [ 39 ] and a tailored approach based on risk is sensible, especially in children. Universal imaging of patients with CT, apart from consuming resources, is not without health risks.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, over 50 % of children undergoing appendectomy in North America have radiation based imaging [ 38 ]. This rate is too high [ 39 ] and a tailored approach based on risk is sensible, especially in children. Universal imaging of patients with CT, apart from consuming resources, is not without health risks.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we found that 98.7% of patients who presented to our hospital with acute appendicitis had a diagnostic US prior to surgery [2]. Only 8.2% underwent evaluation with CT and the majority of CT exams were obtained after an equivocal US.…”
Section: Introductionmentioning
confidence: 82%
“…In the Guite investigation, the mean effective dose for the unindicated phase was 13.1 milliSieverts (mSv), with 33.3% of total examination radiation dose to the study group resulting from unindicated phases [2]. Kim et al [3] reported on data available from 344 children imaged at outside imaging facilities in the setting of acute abdominal pain/possible appendicitis and found that 40% were imaged with suboptimal technique (e.g., wrong phase or multiphase examinations), with multiphase examinations accounting for 17% (60 of 344); 2% were triplephase CT examinations [3]. Of note, the estimated organ doses for the single-phase examinations between the researchers' institution and those from the outside imaging facilities were not significantly different, implying that headway is being made with dose reduction efforts for individual phases but not for the total number of phases.…”
Section: The Landscapementioning
confidence: 99%